Pediatric Anesthetic Management of a Patient With an ALG‐13 Gene Mutation, a Rare Congenital Disorder of Glycosylation - Esha Thakkar; John A. Iasiello; Sunny R. Cai; Adrienne Hutton (Clinical Case Reports)
ABSTRACT Congenital disorders of glycosylation are rare and present a challenge in management due to interactions with intraoperative medications. We present safe and successful anesthetic management of a pediatric patient with an ALG‐13 gene mutation.